Unilateral Adrenal Infarction in Pregnancy: A Case Report - Awatef Hajjaji; Yosra Jemma; Amina Mnejja; Ines Zouari; Imen Ghaddab; Fethi Jebali; Lotfi Gratti; Raja Faleh (Gynecology Obstetrics & Reproductive Medicine)
Adrenal infarction is usually associated with bilateral adrenal hemorrhage in the setting of antiphospholipid syndrome or hemodynamic variation. Few cases of unilateral non-hemorrhagic adrenal infarction have been described in the literature. Here, we report a case occurring during pregnancy. A 27-year-old woman was infected by coronavirus four months ago and presented at 35 weeks of gestation with sudden-onset right abdominal pain without contractions. Unilateral adrenal infarction was diagnosed following computed tomography. It showed an enlarged right adrenal, without hyperenhancement. The patient’s adrenal hormonal function was normal. Accurate diagnosis of non-hemorrhagic adrenal infarction remains difficult as its clinical presentation is not specific. It can only be performed with adrenal imaging. Magnetic resonance imaging shows diffuse enlargement of one or both adrenals and edema on T2-weighted images. Anticoagulation therapy may be discussed. Patients should be evaluated between 3 and 6months after the event to assess adrenal size and function. In summary, non-hemorrhagic adrenal infarction during pregnancy is probably underdiagnosed and obstetricians should be aware of this diagnostic difficulty.